The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1161/circresaha.109.199869
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Putative Serine Carboxypeptidase in Vascular Smooth Muscle Cells

Abstract: Key Words: Scpep1 Ⅲ smooth muscle Ⅲ neointima Ⅲ protease Ⅲ knockout S mooth muscle cells (SMCs) are critical for blood vessel homeostasis, but they also contribute to the pathogenesis of several vasculopathies. In response to arterial injury, SMCs shift from a quiescent, contractile phenotype to a proliferative, synthetic state that undermines normal arterial function leading to neointimal formation. 1,2 Myriad factors and cytokines, as well as proteases and their associated substrates, have been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
(28 reference statements)
0
19
1
2
Order By: Relevance
“…SCPEP1 gene was originally identified in rat aortic smooth muscle cells by screening for retinoid-inducible genes (Chen et al 2001). Lee et al (2009) study demonstrates a role for SCPEP1 activity in modulating smooth muscle proliferation, migration and vascular remodelling. Nothing is known about SCPEP1 gene and function on skeletal muscle but further studies are needed to clarify the role of this serine carboxypeptidase in this specific tissue.…”
Section: Discussionmentioning
confidence: 99%
“…SCPEP1 gene was originally identified in rat aortic smooth muscle cells by screening for retinoid-inducible genes (Chen et al 2001). Lee et al (2009) study demonstrates a role for SCPEP1 activity in modulating smooth muscle proliferation, migration and vascular remodelling. Nothing is known about SCPEP1 gene and function on skeletal muscle but further studies are needed to clarify the role of this serine carboxypeptidase in this specific tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Later study by Lee at al. [27] reported that the Scpep1 -null mice generated by replacing exons 1 and 2 of the Scpep1 gene with Neo cassette show a decrease in medial and intimal cell proliferation as well as in vessel remodelling following arterial injury. The same study also reported that a ∼50% knockdown of endogenous Scpep1 in mouse ASMC line showed dramatic decrease in serum-stimulated growth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive surveying and testing, there are no known substrates for SCPEP1 making this protein an “orphan protease”. Genetic inactivation of SCPEP1 does not show an overt phenotype as mice survive and breed without any histological evidence of pathology[109],[110]. However, upon ligation injury of the carotid artery, SCPEP1 null mice show reduced neointimal load suggesting that SCPEP1 directs VSMC migration and proliferation.…”
Section: Retinoids and Vsmc Phenotypementioning
confidence: 99%
“…However, upon ligation injury of the carotid artery, SCPEP1 null mice show reduced neointimal load suggesting that SCPEP1 directs VSMC migration and proliferation. Indeed, adenoviral delivery of SCPEP1 to VSMC causes accelerated growth and migration in a catalytic triad-dependent manner[110]. Interestingly, SCPEP1 is secreted from cells in a non cleaved manner though it is not clear as yet whether extracellular SCPEP1 exhibits biological activity.…”
Section: Retinoids and Vsmc Phenotypementioning
confidence: 99%